ANALISIS PENERAPAN PRINSIP 3R(REDUCE,REUSE,RECYCLE)PADA PENGELOLAAN SAMPAH RUMAH TANGGA DI RT 04 KELURAHAN TENUN SAMARANDA SEBERANG - Apriyani Apriyani; Sriliyus Agung Susilo; Muhammad Habibi (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2021)
Waste management with 3R principle is a term for waste management principle with Reduce(reducing waste pile) by reducing the use of plastic packaging and replacing it with eco-friendly package. First, reuse ( reuse items) i.g grocery bag made from cloth. Second, recylce (waste recylcing) with the principle of reusing used goods into new useful materials and minimizing the amount of waste to the environment. The purpose of this research was to analyze how the housewives manage their household waste with 3R principle in RT 04 Kelurahan Tenun. The method used in this research was qualitative with phenomenology approach. The informants were housewives, head of RT, and sanitarians of public health center. Then the data analysis used source triangulation techniques. The result showed that the people had not implemented the 3R principle of waste management maximally. The lack of counseling and supporting facilities is a supporting factor so people want to manage good waste management.